Tissue-engineering with muscle fiber fragments improves the strength of a weak abdominal wall in rats. (February 2017) - Jangö, Hanna; Gräs, Søren; Christensen, Lise; Lose, Gunnar
Abstract Introduction and hypothesis Alternative approaches to reinforce the native tissue in patients with pelvic organ prolapse (POP) are needed to improve surgical outcome. Our aims were to develop a weakened abdominal wall in a rat model to mimic the weakened vaginal wall in women with POP and then evaluate the regenerative potential of a quickly biodegradable synthetic scaffold, methoxypolyethylene glycol polylactic-co-glycolic acid (MPEG-PLGA), seeded with autologous muscle fiber fragments (MFFs) using this model. Methods In an initial pilot study with 15 animals, significant weakening of the abdominal wall and a feasible technique was established by creating a partial defect with removal of one abdominal muscle layer. Subsequently, 18 rats were evenly divided into three groups: (1) unrepaired partial defect; (2) partial defect repaired with MPEG-PLGA; (3) partial defect repaired with MPEG-PLGA and MFFs labeled with PKH26-fluorescence dye. After 8 weeks, we performed histopathological and immunohistochemical testing, fluorescence analysis, and uniaxial biomechanical testing. Results Both macroscopically and microscopically, the MPEG-PLGA scaffold was fully degraded, with no signs of an inflammatory or foreign-body response. PKH26-positive cells were found in all animals from the group with added MFFs. Analysis of variance (ANOVA) showed a significant difference between groups with respect to load at failure (p  = 0.028), and post hoc testing revealed that the group with MPEG-PLGA and MFFs showed a significantly higher strength than the group with MPEG-PLGA alone (p  = 0.034). Conclusion Tissue-engineering with MFFs seeded on a scaffold of biodegradable MPEG-PLGA might be an interesting adjunct to future POP repair.